The role of SMEs in sustainable regional development and local business integration: The case of Lublin region (Poland) - Anna Arent; Matylda Bojar; Nelson Duarte; Francisco Diniz (European Regional Science Association (ERSA), 2015)
This paper analyses the role of SMEs in regional development, focusing the particular case of This paper analyses the role of SMEs in regional development, focusing the particular case of Lublin Region in Poland. By using a questionnaire presented to firms that are operating in manufacturing and construction sectors were analysed several issues related to firms themselves, and their sustainability strategies. The sustainability strategy was measured through the combination of the three main perspectives in sustainable development: Economic, Social, and Environmental. This study aims, in a first stage, to analyse entrepreneurs? view of their role in local and regional development, by the adoption of sustainability strategies at the three identified levels. After that, it will also be explored the relation between sustainable development and other variables such as: business local integration, firm age, number of years in the actual location, or firm legal form. As mentioned, the methodology adopted was the questionnaire, in order to get entrepreneurs opinion. In order to guarantee a valid sample, and considering the number of firms operating in this region, it was calculated the number of a valid sample, and due to the results obtained after a pilot study it was identified a valid sample of 44 questionnaires. However, due to the number of firms operating in the manufacturing and construction businesses (above 34.000) it was decided to collect some more questionnaires. At the end 314 questionnaires answered by managers from SMEs operating the in region of Lublin, acting the in the manufacturing and construction sectors, were accepted for this analysis. As main results it was identified that the major concern of entrepreneurs is related to the economic perspective. The second most important perspective was the environmental and at last the social one. In general the results were very positive. Most of firms present a proactive attitude towards to sustainable development, arguing that they adopt sustainability strategies (Economic, Social, and Environmental) at their management policies and strategies. However it was noticed that while older firms (above 10 years old) present greater concern with social and environmental issues, younger firms, are focusing in the economic perspective.
Keywords: M10; O14; O18; O44; 330; SMEs; Sustainable Development; Local/Regional Development